PENERAPAN EVERYONE IS A TEACHER HERE (ETH) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI PESERTA DIDIK - Aini, Izatul; Forcefiati, Tutut; Sudibyo, Elok (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to improve students' communication skills by implementing the Everyone is a Teacher Here (ETH) strategy. This research is action research in the classroom, with the subject being students from class VII-E of SMP Negeri 1 Porong. The instruments used to collect data were observation sheets and tests. This research data was collected through tests, observations, and interviews. The research was carried out in two cycles, with cycle I taking place in one meeting (3 x 40 minutes) and cycle II taking place in one meeting (3 x 40 minutes) as well. The research results showed a significant increase. The average percentage of students' communication skills in the six indicators in cycle 1 is 43.75%, which is in the medium category, and in cycle 2, it is 75%, which is included in the high category. ETH learning strategies can improve communication skills and increase students' participation and enthusiasm for learning in learning activities.